2012
DOI: 10.1007/s11434-011-4880-6
|View full text |Cite
|
Sign up to set email alerts
|

Forward acoustic scattering by moving objects: Theory and experiment

Abstract: The normal mode model for scattering in shallow water is employed to investigate the forward scattering with a target crossing the source-receiver axial line. An experiment was conducted in a littoral environment to analyze forward scattering by a slowly moving object. The theoretical and experimental results show that the sound field aberration takes minimum values if the object is located mid-point along the source-receiver line, whereas it attains its maximum if the object is close to the source or receiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…When only one path exists for the signal, matrix K decreases to one dimension, and the expression is similar as (30) in [24]. The test statistic can be further expressed as…”
Section: Glrt Derivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…When only one path exists for the signal, matrix K decreases to one dimension, and the expression is similar as (30) in [24]. The test statistic can be further expressed as…”
Section: Glrt Derivationsmentioning
confidence: 99%
“…In the event of the intruder crossing the source-receiver line, an aberration in the received signals occurs due to the interference between the direct blast and scattered signal. When an object crosses at midpoint between the source and receiver, the acoustic field aberration is at the minimum [30]. Hence, to show the performance of the method in forward detection, a worse situation is considered in the simulation.…”
Section: Experimental Configurationmentioning
confidence: 99%
“…In summary, despite the different applications of existing three mainstream video encryption schemes in different application fields owing to their respective advantages and disadvantages, tradeoff problems are widely present in the aspects of security and compression ratio, security and operability, as well as security and universality. This paper preferably solves the tradeoff between security and real-timeliness through the encryption of moving objects only [9].…”
Section: Research Status and Requirements On Video Encryptionmentioning
confidence: 99%
“…At the laboratory scale, Marandet et al [7] experimentally demonstrated the detection and localization of a wavelength-sized target in a shallow ultrasonic waveguide between two source-receiver arrays at 3 MHz. Lei et al [8], [9] further combined PCA with array processing to enhance the aberrations of the recorded direct arrival data on a short vertical receiver array (VRA), validated the performance of the proposed method on the basis of a lake experiment, and identified the relationship between sound field aberration and crossing distance in theory and experiment. The adaptive processing scheme and PCA-based concept are executed after acquiring several pulses.…”
Section: Introductionmentioning
confidence: 99%